Research on the Existing Problems and Optimization Strategies of Nike sports Goods Brand Marketing - Kang, Jiaqi (BCP Business & Management, 2022)
Nike is a well-known sports brand globally; It not only includes clothes and shoes but also creates a lot of sports goods. Nike’s performance in the Chinese market in recent years is not very good, and other established overseas sports brands have also suffered setbacks in the Chinese market. Nike, for example, reported annual revenue from Greater China of $7.547 billion in 2022, down 9% from a year earlier. It’s not just Nike. Adidas reported its Q2 2022 financial results on August 4, 2022, with a net profit of 3.09 euros, down 24.2% from a year earlier. Based on Nike’s major marketing strategies in China from 2019 to 2022, this paper discusses the changes Nike can make in its sales strategies in the future and analyzes the Chinese market environment to find out the opportunities, advantages, and disadvantages Nike currently has in the Chinese market. To achieve the integration of brand culture and do a good job of localized marketing, develop the sporting goods market while striving for market space for Nike.